Possibilities of Interpreting the Night-to-Day Ratio Specified by 24-Hour Blood Pressure Monitoring. (1st February 2023) - Havelkova, Alena; Dvorak, Petr; Siegelova, Jarmila; Dobsak, Petr; Filipensky, Petr; Cornelissen, Germaine
Abstract : Aim . Specify the risk rate of incorrect patient classification based on the night-to-day ratio specification from singular 24-h ABPM in comparison to the results of 7-day ABPM monitoring Materials and Methods . 1197 24 h cycles were enrolled in 171 subjects in the study and divided into 4 groups: group 1 (40 healthy men and women without exercise), group 2 (40 healthy exercise-training men and women), group 3 (40 patients with ischemic coronary artery disease without exercise), and group 4 (51 patients with ischemic coronary artery disease following cardiovascular rehabilitation). The subject of the evaluation was the percentage rate of incorrect subject classification (dipper, nondipper, extreme dipper, and riser) based on the mean blood pressure values for 7 days and from seven independent 24-hour cycles (the mean value mode). Results . In the case of the individuals included in the monitored groups, the mean night-to-day ratio-based (mode for the 7 days versus the individual days of 24-hour monitoring) classification accordance ranged between 59% and 62%. Only in singular cases did the accordance reach 0% or 100%. The accordance size was not dependent on the health or cardiovascular disease (p < 0.594 ; 56% vs. 54%) or physical activity (p < 0.833 ; 55% vs. 54%) of the monitored individuals. Conclusion . The specification of the night-to-day ratio of each individual for each day of the 7-day ABPM monitoring would be the most convenient option. In many patients, diagnosing could thus be based on the most frequently occurring values (mode specification). The study protocol was registered with ClinicalTrials.gov (NCT05264090 )